1988
DOI: 10.1300/j013v14n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Noncomformity and Perception of Mental Illness

Abstract: The hypothesis that clinicians' perceptions of psychological maladjustment are related to the deviation of symptoms from prevailing gender role stereotypes was explored. Case history descriptions were sent to a random sample of practicing psychologists. These clinicians viewed female patients with "masculine" symptoms (e.g., alcoholism or antisocial behavior) as more psychologically disturbed than males with the same symptoms; they also perceived male patients with "feminine" symptoms (e.g., depression and anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…This is driven by perceptions of decreased dangerousness and volatility. Furthermore, studies of health professionals have mirrored the findings reported by the general public in that there appears to be a gender difference in perceptions of evaluators of mental health patients based on the gender of the patient (Waisberg & Page, 1988). Additionally, it was found men and women who suffered from mental health issues, and exhibited symptoms that did not match gender norms, were stigmatized more severely by evaluators than if their symptoms were congruent with gender norms (Prout & Fredrickson, 1991;Rabinowitz & Lukoff, 1995).…”
Section: Gender and The Stigma Of Mental Health Problemsmentioning
confidence: 79%
“…This is driven by perceptions of decreased dangerousness and volatility. Furthermore, studies of health professionals have mirrored the findings reported by the general public in that there appears to be a gender difference in perceptions of evaluators of mental health patients based on the gender of the patient (Waisberg & Page, 1988). Additionally, it was found men and women who suffered from mental health issues, and exhibited symptoms that did not match gender norms, were stigmatized more severely by evaluators than if their symptoms were congruent with gender norms (Prout & Fredrickson, 1991;Rabinowitz & Lukoff, 1995).…”
Section: Gender and The Stigma Of Mental Health Problemsmentioning
confidence: 79%
“…Alternatively, people with inconsistent sex and mental illness sex-type (men with a feminine sex-typed illness or women with a masculine sex-typed illness) may be viewed negatively because of the gender role deviance implied by such inconsistency (e.g., Baskin, Sommers, Tessler, & Steadman, 1989;Rosenfield, 1982;Waisberg & Page, 1988). However, Wirth and Bodenhausen (2009) found the opposite effect: Individuals with gender atypical mental illnesses were evaluated more favorably because the illness was seen as more likely to be a genuine, biologically based mental disturbance (see also Sprock, Crosby, & Nielsen, 2001).…”
Section: Prejudice Toward People With Multiple Category Membershipsmentioning
confidence: 99%
“…Fueling the biases concerning abortion are the prevailing biases against women. Some psychotherapists have been found to hold views of women that are based on traditional gender roles, which are reinforced by their training, and affect the diagnoses and treatment they provide (Teri, 1982;Waisberg & Page, 1988;Weiner & Boss, 1985;"Summary and Recommendations," 1984). Sherman, Koufacos, and Kenworthy ( 1978) found psychotherapists held stereotypical attitudes and information about women that were often contradictory to the attitudes and information provided by their women patients.…”
Section: Therapist Biasmentioning
confidence: 99%